Call me and I’ll go: the effect of shop window display on buying behavior of Brazilian customers in fashion retail - Scussel, Fernanda Bueno Cardoso; Pujol Filho, Francisco; Petroll, Martin de La Martinière; Damacena, Cláudio (Revista de Administração da UFSM, 2020)
From a theoretical reference on consumer behavior in traditional retail, this article explores the role of window display as a predictor of store entry and purchase decision. The study carried out in a Brazilian capital is a replication of Sen, Block and Chandran’s (2002) seminal research and had 364 participants. Data were analyzed by structural equation modeling. Results indicate fashion trend, price and sale information as the main drivers of the decision to enter the store, which is the most relevant factor for consumers when deciding to buy a product. These findings confirm not only the relationship between window display and decision making, but they reveal window display as an antecedent of consumer decision making in traditional retail. Additionally, our findings show the sensitivity of Brazilian consumer to novelty and fashion trends, as well as their predisposition to enter stores and purchase products when they are on sale or when payment alternatives are announced. Regarding academic contributions, this is a first step in understanding retail shopping experience, being window display the staring point. Thus, studies on store atmosphere, visual identity construction as well as price strategies can benefit from this content. Considering also the growth of e-commerce and the need to attract consumers to the physical stores, these results contribute to the studies on retail business strategies, suggesting the relationship between the effect provoked by window displays and business performance.